2014
DOI: 10.33549/physiolres.932788
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormones in the Development of Postpartum Depression

Abstract: Postpartum depression affects 10-15 % women after childbirth. There is no currently generally accepted theory about the causes and mechanisms of postpartum mental disorders. The principal hypothesis concerns the association with sudden changes in the production of hormones affecting the nervous system of the mother and, on the other hand, with the ability of receptor systems to adapt to these changes. We observed changes in steroidogenesis in the period around spontaneous delivery. We collected three samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…It is noteworthy that the fetus and placenta, as well as maternal gonadal glands, produce gonadal steroids; therefore, the delivery of the fetus and placenta should theoretically have an impact on the drop in the concentration of gonadal steroids in women through the loss of the additive production of gonadal steroids from the fetus and placenta. Only one study with a fairly small sample size (44 mothers) reported a correlation between gonadal steroid levels in umbilical cord blood and maternal mental health (Parizek et al, 2014). Higher levels of estradiol and progesterone were observed in the umbilical cord blood of newborns with mothers who developed some degree of depression in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that the fetus and placenta, as well as maternal gonadal glands, produce gonadal steroids; therefore, the delivery of the fetus and placenta should theoretically have an impact on the drop in the concentration of gonadal steroids in women through the loss of the additive production of gonadal steroids from the fetus and placenta. Only one study with a fairly small sample size (44 mothers) reported a correlation between gonadal steroid levels in umbilical cord blood and maternal mental health (Parizek et al, 2014). Higher levels of estradiol and progesterone were observed in the umbilical cord blood of newborns with mothers who developed some degree of depression in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, regarding physical and genetic factors influencing depression, Seney et al [ 72 ] showed that sex chromosome complement regulates expression of mood-related genes. Pařízek et al [ 73 ] demonstrated that the strongest correlations between steroid and postpartum depression change. Other variables other than demographic variables were not included in this study, which is a limitation of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In the postpartum and peripartum period, androgens correlated in humans with mood disorders. Androgen levels in venous blood samples collected from mothers after childbirth correlated positively with severity of depressive symptoms [46]. Markedly elevated testosterone levels were measured in postpartum depression at 24-28 h after childbirth, when compared to controls.…”
Section: Androgen Receptor (Ar) As a Possible Modulator Of Central Mamentioning
confidence: 93%